2016
DOI: 10.1007/s10876-016-1037-4
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles Using Water Extract from Galls of Rhus Chinensis and Its Antibacterial Activity

Abstract: The green synthesis of silver nanoparticles (AgNPs) has been proposed as a simple, eco-friendly and cost effective alternative to chemical and physical methods. The Rhus chinensis plant is one of the well studied medicinal plant and its galls find excellent clinical and therapeutic applications. The present study reports the use of water extract from galls of R. chinensis as a reducing agent and formation of AgNPs from silver nitrate solution by a green synthesis route. The AgNPs formation was observed visuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The zones of inhibition observed against the test pathogens were lower than those obtained in PANF. The antimicrobial activity of the nanoparticles supports the previous observation reported in literature in AgNPs synthesized with R. chinensis galls extract and marine algae (Ecklonia cava) respectively [55,56]. Contrary to the above observations, antibacterial activities of the synthesized nanoparticles against Salmonella Typhimurium and Salmonella Enteritidis were not dependent on concentration of Fe 3 O 4 NPs.…”
Section: Photocatalytic Activitysupporting
confidence: 89%
“…The zones of inhibition observed against the test pathogens were lower than those obtained in PANF. The antimicrobial activity of the nanoparticles supports the previous observation reported in literature in AgNPs synthesized with R. chinensis galls extract and marine algae (Ecklonia cava) respectively [55,56]. Contrary to the above observations, antibacterial activities of the synthesized nanoparticles against Salmonella Typhimurium and Salmonella Enteritidis were not dependent on concentration of Fe 3 O 4 NPs.…”
Section: Photocatalytic Activitysupporting
confidence: 89%
“…The S. aureus colonies treated with 40 µg of AgNPs exhibited a larger diameter of zone of inhibition ( Figure 8 (Bd)), as compared to those treated with aqueous extract of Ecklonia cava alone ( Figure 8 (Bb)). It was reported that synthesized AgNPs with Rhus chinensis extracts exhibited efficient antimicrobial activity against S. aureus, Staphylococcus saprophyticus , E. coli , and Pseudomonas aeruginosa [ 61 ]. This study used 50 µg to 70 µg of AgNPs to achieve good antibacterial activity against all of the tested bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial activity of biosynthesized AgNPs against microorganisms was assessed by an agar well diffusion method as previously described [ 61 ]. Briefly, both Escherichia coli and Staphylococcus aureus were cultured in 3 mL of Luria–Bertani broth.…”
Section: Methodsmentioning
confidence: 99%
“…The cell wall of Gram-negative bacteria is made up of thin peptidoglycan layer while that of Gram-positive bacteria is made up of thick peptidoglycan layer [39]. The antimicrobial activity also depends on nanoparticle concentration used and the type of bacterial species [40].…”
Section: Antimicrobial Activitymentioning
confidence: 99%